Daily field checking list by Walter Rosene, March 26, 1933 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated March 26, 1933. This checklist was used by Walter Rosene to record birds sighted around McCaskey Pasture and North Pond with Bob Walker. Plustek--flatbed